An association and genetic polymorphisms of CYP2D6 gene in chronic renal failure patients in AL- Qadisiya province / Iraq. - Shurooq H. Jaber (Al-Qadisiyah Journal of Pure Science, 2017)
The gene CYP2D6 is one of the most important genes of phase I drug metabolizing enzymes. Individuals differ in response to drugs caused by mutation in CYP2D6 gene. The patients with chronic renal failure disease (CRF) are often treated with more than one drug. This study was designed to investigate the distribution of CYP2D6 polymorphism in patients with CRF and also to evaluate the role of this polymorphism gene as a genetic risk modifier in the etiology of CRF disease.The study was carried out on (60) patients with CRF and (60) healthy volunteers . The CYP2D6 genotypes were analyzed by (PCR- RFLP) method.The results indicated that the levels of creatin and urea were significantly higher (P < 0.05) in CRF patients compared to control. While the mean Hb concentration, PCV level were significantly lower(P < 0.05) in CRF patients compared with healthy subjects. There was no significant association between CRF risk and CYP2D6 (HEM) genotype. The nonfunctional CYP2D6 (PM) genotype had a (1.89) fold increase of risk toward CRF disease the (95 % CI= 0.18-12.32). This study showed the protective CYP2D6 (EM) in CRF severity.The statistical analysis showed no significant association between the age and CYP2D6 (HEM, EM)genotypes.The risk for developing CRF disease increased in case of heavy smokers of (1.6) fold as compared to light smokers (OR= 1.2).